Endogeneity of money supply: Evidence from Malaysia - Nayan, Sabri; Chik, Abdul Razak (ASEAN Universities Consortium of Enterpreneurship Education (AUCEE), 2010)
Money is the blood of modern free-enterprise economies. Correspondently, the quantity and velocity of money circulated in such an economy would determine its health. Expressed differently, the levels of economic activities, production and money supply in an economy are interrelated. The central issue then is, does the quantity of money supply determine the levels of economic activities and production? Or, on the contraly, are economic activities and production the variables that actually determine the level of money supply in an economy? Indeed the endogeneity/exogeneity of money supply is still an unsettled issue. While nobody can still say for sure whether the supply of money is endogenously or exogenously determined, this issue is crucial for a proper formulation of macroeconomic theory and policy. Since, as previously noted, the economic health of a countv would depend heavily on its money supply. Having said this, if we were to obtain some valuable insights into efective and efficient management of an economy, this issue needs to be examined and analyzed rigorously. In much of the mainstream macroeconomic literature money supply is assumed to be exogenously determined by the central bank. This view is put forward by a group of economists known as the Monetarists based on the argument that money supply equals the money multiplier times the monetaly base. Since the central bank can change this base, it can control the supply of money in the economy. On the other side of the debate, another group of economists known as Post Keynesian Economists maintain that money supply is endogeneity, in nature. Whereas, there are a number of different views of the concept of money supply endogeneity, the core argument of this school of monetary economic thought is that bank lending creates deposits and hence money supply. Given such opposing views on exogeneity/endogeneity of money supply, the central issue at this juncture is: does loan cause money supply or does money supply cause loan? Accordingly, our study will examine this issue by using cointegration test and vector error correction model developed by Johansen. The results of this study have enabled us to claim convincingly that lending is an essential (endogenous) determinant of money supply in Malaysia. Findings of the study clearly corroborates Horizontalist view of money supply endogeneity that in Malaysia, loan causes monetary aggregates (i.e.,M0, M1, M2, and M3).